Modelling fracture formation and propagation in geo-materials - Maedo, Michael A.; Sánchez, Marcelo; Guimarães, Leonardo; Manzoli, Osvaldo; Cleto, Pedro (EDP Sciences, 2019)
The modelling of fracture formation and propagation in geo-materials is a subject of interest in several problems and applications. In this work, finite elements with high aspect ratio are used to study the hydraulic fracture process in the context of conventional continuum constitutive (stress-strain) relationships based on the damage theory. The deformable porous material is solved in a coupled manner by considering a fully hydro-mechanical approach. The adopted approach is explained and validated against analytical and numerical solutions.